FACTORS INFLUENCING STRATEGIC RESPONSES TO EXTERNAL ENVIRONMENT BY DEPOSIT TAKING SACCOS IN NAIROBI COUNTY: A STUDY OF UNAITAS SACCO - Abdow, Salat Khalif; Ogollah, Dr. Kennedy (Journal of Strategic Management, 2016)
Purpose: The purpose of this study was to determine the factors influencing strategic responses to external environment by deposit taking SACCOS in Nairobi County: a study of Unaitas Sacco. Methodology: The research adopted case study research design. The target population of the study was 11 directors and 600 employees of Unaitas Sacco. The sample size consisted of 61 (10% of the target population) directors and employees of Unaitas Sacco. Stratified random sampling was used in the study to select the one director and the 60 employees of Unaitas Sacco. The study used primary data. The data collection instruments that were used in this study were the interview guide and questionnaire. The qualitative analysis was done using content analysis. Quantitative data analysis employed descriptive statistics and factor analysis. Descriptive statistics included frequencies, percentages, means and standard deviation. Results were presented in form of tables and charts. Particular statistics in factor analysis was scale plot and commonalities. Results: The study found that reference to past strategy organization external dependence, consideration of level of risk and Organizational Culture greatly influences the choice of strategic response. In addition managerial competence, organizational structure and control processes, time available and availability of resources also greatly influence the choice of strategic response Unique contribution to theory, practice and policy: The study recommends that Unaitas to invest more in the latest technology and start agency banking as a strategy of expanding its market share and product differentiation.